Age-related Macular Degeneration - Holz, Frank G.; Pauleikhoff, Daniel; Spaide, Richard F.; Bird, Alan C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Age-related macular degeneration has become the most common cause of blindness. With population ageing AMD will become an ever more prevalent cause of visual loss. Here, an expert panel of experienced clinicians and eminent basic scientists provide an authoritative review on the pathogenesis, epidemiology and risk factors, diagnostic methods, imaging modalities and treatment strategies for age-related macular degeneration. Many excellent photographs and diagrams add to a clear understanding.
Pathophysiology: Epidemiology -- Genetics of AMD -- Aging of the Retina and Retinal Pigment Epithelium -- Complement System -- Current Concepts in AMD-Pathogenesis. Clinical Manifestations: Early AMD -- Neovascular AMD -- Geographic Atrophy. Diagnostics: Fluorescein- und ICG-Angiography -- Optical Coherence Tomography -- Microperimetry. Prophylaxis and Therapy: Nutritional Supplementation -- Laser Photocoagulation and Photodynamic Therapy -- Anti-VEGF-Therapy: Basic Information and Substances -- Anti-VEGF-Therapy: Results and Guidelines -- Combination Therapies for the Treatment of AMD -- Treatment Approaches for Dry Atrophy -- Surgical Therapy. Rehabilitation: Reading Ability -- Magnifying Visual Aids.
Keywords: Medicine; Geriatrics; Diabetes; Ophthalmology; Medicine & Public Health; Ophthalmology; Geriatrics/Gerontology.; Diabetes